LEGAL PROTECTION FOR COPYRIGHT WORKS OF ART IN THE DIGITAL ERA IN INDONESIA - Micael Jeriko Damanik; Rolando Marpaung; Dikki Saputra Saragih; Parlindungan Purba; Lidya Lase (PT. Radja Intercontinental Publishing, 2023)
Current technological developments have greatly influenced the field of Intellectual Property Rights. Internet technology with its various conveniences not only provides benefits for copyright but also causes losses which have an impact on increasing violations of copyright law in Indonesia, especially digital copyright. Legal protection for copyright based on digital technology in Indonesia culminates in Law Number 28 of 2014 concerning Copyright. Copyright law has basically accommodated technological developments in Indonesia, but law enforcement in cases in the digital sector provides protection for copyright based on government law. The law must also be applied appropriately, so that developing digital technology does not damage the basic principles of copyright